2019
DOI: 10.3390/s19122798
|View full text |Cite
|
Sign up to set email alerts
|

A New Design of an MOEMS Gyroscope Based on a WGM Microdisk Resonator

Abstract: In this paper, we present a new design for a micro-opto-electro-mechanical (MOEMS) gyroscope based on a whispering-gallery mode (WGM) microdisk resonator and MEMS resonator. The mechanical characteristics, frequency split, and quality factor (Q) of the MEMS resonator; the optical characteristics, Q value, and coupling regimes of the WGM resonator; and the coupling between the two resonators were analyzed. Its operation principle—the transformation process from angular velocity to the resonance wavelength of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Moreover, based on the MOEMS techniques, in 2020, D. Xia et al [114][115][116] reported an electrostatically driven MEMS gyroscope with the nested ring structure and detected by the whispering gallery mode (WGM) mode, as shown in Fig. 8(d).…”
Section: Nested Ring Micro-gyroscopementioning
confidence: 99%
“…Moreover, based on the MOEMS techniques, in 2020, D. Xia et al [114][115][116] reported an electrostatically driven MEMS gyroscope with the nested ring structure and detected by the whispering gallery mode (WGM) mode, as shown in Fig. 8(d).…”
Section: Nested Ring Micro-gyroscopementioning
confidence: 99%
“…The broadband sensor was siliconbased [11]. A WGM gyroscope was shown to have a 3.002 pm/(°.s -1 ) [12]. Dual measurements of refractive index changes and pressure were conducted using a WGM resonator.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the refractive index of the environment [ 16 ], temperature [ 17 , 18 , 19 ], humidity [ 20 ], greenhouse gases [ 21 ] and deformation [ 22 ] can be measured by these kinds of sensors. In addition, the microcavities can be used as a gyroscope [ 23 ]. Using microcavities, it is also possible to create stable compact narrow-band laser systems [ 24 , 25 ] and to generate optical frequency combs [ 26 ] including soliton ones [ 27 ].…”
Section: Introductionmentioning
confidence: 99%